Evaluation of ultrafine particle concentrations and size distributions at London Heathrow Airport. (1st February 2020) - Stacey, Brian; Harrison, Roy M.; Pope, Francis
Abstract: A study to monitor UFP at Heathrow Airport was undertaken in the autumn of 2016. The objective was to assess the context of measurements at the airport compared to measurements at "typical" traffic, background and rural locations in the south east of England. Measurements were made at two airport locations (called LHR2 and Oaks Road) at opposite ends of the airfield, to further understand the contribution of the airport to local air quality. Average concentrations showed that total particle number concentrations at the airport are typically lower than a traffic location and higher than an urban background location in London, matching the trends seen for NOx, PM10, PM2.5 and BC pollutants. However, the size distribution of the submicrometre particles at the airport is completely different to the London monitoring stations, with the airport PSD dominated by particles with a mode of 20 nm. In contrast, measurements of PN in London have a significantly larger mode of 30 nm. This study demonstrated that measurements of particle number from within the airport perimeter are dominated by the smallest particles and are closely associated with aircraft. Analysis of the operating modes at the airport showed that aircraft departing from the airport emit particles in much higher numbers than those arriving. Nucleation mode particles are commonly associated with emissions from combustion processes. However, measurement of these particles at the airport are not strongly correlated with Black Carbon. There does appear to be some correlation of nucleation mode particles with UV active BC particles (brown carbon, typically associated with biomass combustion or wood smoke) at the Heathrow airside monitoring station, LHR2. There is also modest association between nucleation mode particles and NO2 . The study showed that the classical air pollutants measured at Heathrow are very similar in concentration to typical urban environments in London and south east England, but particle numbers in the sub 30 nm size range are markedly different to those measured in London. Highlights: UFP close to Heathrow Airport is different to typical urban locations in London. UFP at the airport is closely associated with departing and landing aircraft. UFP measurements are strongly dependent on prevailing wind direction. UFP measurements are highest from departing aircraft. UFP measurements are only reasonably correlated with nitrogen dioxide.